2017
DOI: 10.20902/ijptr.2017.1019
|View full text |Cite
|
Sign up to set email alerts
|

Solid Phase Extraction-HPLC Method for Determination and Pharmacokinetic Study of Garenoxacin in Rat Plasma after Oral Administration

Abstract: :A method based on solid phase extraction was developed for the determination of Garenoxacin in rat plasma after oral administration by high-performance liquid chromatography coupled with PDA detection (HPLC-PDA). Variables parameter affecting the solid phase extraction efficiency were evaluated and optimized. Chromatography separation was performed on a THERMO, BDS HYERSIL C18 column (4.6 mm × 100mm, 5µ) by isocratic elution with PDA detection at 279 nm. The assay was linear over the range of 15-44 μg/ml and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…GRN is utilized in the treatment of certain respiratory tract diseases, Urinary tract infection, otorhinolaryngological infections and Penicillin and fluoroquinolone-resistant Streptococcus pneumonia [2]. A compressive literature survey revealed that, fewer analytical methods viz RP-HPLC has been reported for estimation of GRN in pharmaceutical dosage form [3,4] and in biological samples [5]. Also, Spectrophotometry methods [6 -8] have been established.…”
Section: Introductionmentioning
confidence: 99%
“…GRN is utilized in the treatment of certain respiratory tract diseases, Urinary tract infection, otorhinolaryngological infections and Penicillin and fluoroquinolone-resistant Streptococcus pneumonia [2]. A compressive literature survey revealed that, fewer analytical methods viz RP-HPLC has been reported for estimation of GRN in pharmaceutical dosage form [3,4] and in biological samples [5]. Also, Spectrophotometry methods [6 -8] have been established.…”
Section: Introductionmentioning
confidence: 99%